Capturing Risks and Potentials for Microfinance Sustainable Growth in Cameroon - Gérard, Tchouassi; Thaddeus Jini, Bomnsa; Roland Azibo, Balgah (European Journal of Sustainable Development, 2018)
This study captures the relationship of risks, potentials and microfinance sustainable growth in Cameroon where growth has been particularly favored by increased unreliability of the formal banking sector. However, significant improvements currently observed in the latter sector present a new form of risk. How MFIs will survive in the face of a vibrant commercial banking sector in Cameroon is not fully researched. Empirical data from the North West region of Cameroon was purposively and randomly selected for the case study of two Microfinance institutions, CamCCUL and MUGFIC PLC. Collected quantitative data was analyzed. It was observed that CamCCUL clients were generally less exposed to risks than MUGFIC ones (99% and 94% respectively; X2=0.03. On the contrary, MUGFIC generally engaged in riskier activities than CamCULL (P=0.000). These risks can however be significantly minimized through improved risk management strategies to further mitigate risks in the MF sector in Cameroon. Key words: risks, potentials, microfinance, sustainable growth, poverty, Cameroon